Comparison of subantarctic mode water and Antarctic intermediate water formation rates in the South Pacific between NCAR-CCSM4 and observations - Hartin, CA; Fine, RA; Kamenkovich, I; Bernadette Sloyan (2014)
Average formation rates for Subantarctic Mode Water (SAMW) and Antarctic Intermediate Water (AAIW) in the South Pacific are calculated from the National Center for Atmospheric Research Community Climate System Model version 4 (NCAR-CCSM4), using chlorofluorocarbon inventories (CFC-12). When compared to observations, CCSM4 accurately simulates the southeast Pacific as the main formation region for SAMW and AAIW. Formation rates for SAMW in CCSM4 are 3.4 sverdrup (Sv), about half of the observational rate, due in part to shallow mixed layers, a thinner SAMW layer, and insufficient meridional transport. A formation rate of 8.1 Sv for AAIW in CCSM4 is higher than observations due to higher inventories in the southwest and central Pacific and surface concentrations within CCSM4. Also, a lack of data in the southwest Pacific may bias the observational rate low. This model-observation comparison is useful for understanding the uptake and transport of other gases, e.g., CO 2 by the model.